The collapse of sensemaking at Yarnell Hill : the effects of endogenous ecological chaos on enactment - Parrish, Dan (2021)
Purpose – Since Weick’s (1993) seminal Mann Gulch paper articulated a collapse of sensemaking, scholars have repeatedly investigated sensemaking downstream of enactment. Motivated by another wildland firefighting tragedy, the tragic loss of 19 firefighters in Arizona in 2013, this study aims to look at enactment itself and reveals that the endogenous creation and re-creation of the wildland fire caused a fatal feedback loop of “trigger traps” leading to perpetual enactment that short-circuited sensemaking. Wildland fires can have unpredictable consequences, which triggers in individual sensemakers a fatal and continuous return to the beginning of the sensemaking process. Design/methodology/approach – This paper’s approach is a case study based on a textual analysis of sources investigating the 2013 Yarnell Hill fire. The authors also carefully compared the Yarnell Hill and Mann Gulch disasters in search of breakdowns in sensemaking that could help us understand why we continue to lose firefighters in the line of duty. Findings – The simultaneously volatile and complex environment at Yarnell illustrates sensemaking antecedents to the study of enactment. The findings suggest ways that organizations – those fighting wildfire or those fighting a global pandemic – can avoid getting trapped in the early stages of enactment and can retain resilience in their sensemaking. Originality/value – This paper introduces the concept of “trigger traps” to help explain the fatal feedback loop of repeated environmental triggers in the early stages of sensemaking in volatile environments.